The Effect of IFRS Adoption on Supply Chain Management and Earnings Persistence - Amrie Firmansyah; Silmiana Nisa Fadila (International Journal of Supply Chain Management, 2020)
Abstract. This study aims to examine the effect of the International Financial Reporting Standards (IFRS) adoption on supply chain management and earnings persistence. This research is quantitative research with multiple linear regression models. The sample used in this research is manufacturing companies listed on the Indonesia Stock Exchange (IDX). The type of data used in this study is secondary data in the form of financial statements and annual companies listed on the Stock Exchange from 2009 to 2015. The sample selection using a purposive sampling method with the number of samples of 66 companies, so that the overall sample amounted to 462 observations. This study uses data with the same number of years for three years, so that this paper is research with panel data. The results that IFRS had significant association with supply chain management. A better implementation of international financial reporting, as a set of principle-based standards is the key to enhance the supply chain management for earning managements.